Structural Revision of Natural Cyclic Depsipeptide MA026 Established by Total Synthesis and Biosynthetic Gene Cluster Analysis. (8th March 2021) - Uchiyama, Chihiro; Fukuda, Akane; Mukaiyama, Minagi; Nakazawa, Yoshiki; Kuramochi, Yuka; Muguruma, Kyohei; Arimoto, Mitsue; Ninomiya, Akihiro; Kako, Koichiro; Katsuyama, Yohei; Konno, Sho; Taguchi, Akihiro; et al.
Abstract: A revised structure of natural 14‐mer cyclic depsipeptide MA026, isolated from Pseudomonas sp. RtlB026 in 2002 was established by physicochemical analysis with HPLC, MS/MS, and NMR and confirmed by total solid‐phase synthesis. The revised structure differs from that previously reported in that two amino acid residues, assigned in error, have been replaced. Synthesized MA026 with the revised structure showed a tight junction (TJ) opening activity like that of the natural one in a cell‐based TJ opening assay. Bioinformatic analysis of the putative MA026 biosynthetic gene cluster (BGC) of RtIB026 demonstrated that the stereochemistry of each amino acid residue in the revised structure can be reasonably explained. Phylogenetic analysis with xantholysin BGC indicates an exceptionally high homology (ca. 90 %) between xantholysin and MA026. The TJ opening activity of MA026 when binding to claudin‐1 is a key to new avenues for transdermal administration of large hydrophilic biologics. Abstract : A revised structure of natural cyclic depsipeptide MA026 with tight junction opening activity was established by physicochemical analysis and confirmed by its total solid‐phase synthesis. Bioinformatic analysis of the putative MA026 biosynthetic gene cluster demonstrated that the stereochemistry of amino acid residue in the revised structure can be reasonably explained.